Twenty-four buried ice masses remotely mapped in Transantarctic Mountains, Antarctica - Jaakko Putkonen; Taufique H. Mahmood (Geocarto International, 2023)
Glacial ice contains information on paleoclimate, but typically is less than 1 Myrs old because glaciers continuously flow and melt. A recently discovered buried ice mass in Antarctica is dated to 3-5 Myrs and highlights the potential for long preservation of ancient ice under a layer of debris. Only two such ice masses are so far known in Antarctica. Given the significant scientific potential and lack of systematic mapping, we set out to locate all buried ice masses in Transantarctic Mountains (TAM). We visually analyzed >8,000 high-resolution satellite images covering much of the TAM. We searched for the polygonal patterned ground that signifies ice in the ground and once detected the corresponding digital elevation model was inspected for presence of a convex landform. When both features coincide, they indicate the presence of a buried ice body. We identified 22 new sites that are likely to conceal massive buried ice masses.